AKSELERASI INVESTASI: FAKTOR EKONOMI DAN NON EKONOMI - Aulya Rahma T (RJABM (Research Journal of Accounting and Business Management), 2026)
This study aims to analyze the acceleration of investment in Indonesia by integrating both economic and non-economic factors. Using a qualitative approach with descriptive-analytical methods, the research relies on secondary data from various institutional and academic sources. The findings show that stable macroeconomic conditions such as consistent economic growth, controlled inflation, and stable exchange rates form the foundation for investment expansion. However, investment acceleration is significantly influenced by non-economic factors including legal certainty, regulatory quality, government effectiveness, and corruption control. The study highlights that the synergy between economic stability and institutional reforms determines the sustainability of investment inflows. Thus, a comprehensive and integrated policy approach is essential to enhance investment acceleration and support Indonesia’s long-term development goals toward Vision 2045.Keywords: investment acceleration, macroeconomic stability, institutional quality, regulation, economic growth, governance.